The Relationship between Metacognitive Awareness, Self-Efficacy and Learning Motivation on Biology Learning Outcomes for Class XI State High School Students in Soppeng Regency - Wirna Arsyad; Muhiddin Palennari; Alimuddin Ali; Firdaus Daud; Yusminah Hala (Postgraduate, University of Mataram, 2026)
This study aims to analyze the relationship between metacognitive awareness, self-efficacy, and learning motivation on biology learning outcomes of eleventh-grade students in public high schools in Soppeng Regency, both directly and indirectly. This quantitative study employed an ex post facto correlation approach with Structural Equation Modeling (SEM) analysis techniques. A sample of 505 students was selected using simple random sampling and proportional sampling techniques from a total population of 1.444 students. The instruments used included questionnaires on metacognitive awareness, self-efficacy, and learning motivation, as well as a biology learning achievement test. The results showed that metacognitive awareness was significantly related to learning motivation (p=0.00), but had no direct effect on learning outcomes (p=0.06). Self-efficacy was significantly related to learning outcomes (p=0.01), but not significantly to learning motivation (p=0.06). Learning motivation was also significantly related to learning outcomes (p=0.00). Indirectly, metacognitive awareness has a significant relationship with learning outcomes through the mediation of learning motivation (p=0.00) and self-efficacy (p=0.02). However, the indirect relationship between self-efficacy and learning outcomes through learning motivation was not significant (p=0.16). The conclusion of this study confirms that learning motivation plays a crucial role as a primary mediator. Increasing metacognitive awareness and self-efficacy needs to be optimized in an integrated manner to improve student learning outcomes.